KINERJA MANAJERIAL LPD DALAM PERSPEKTIF PARTICIPATIVE BUDGETING, KOMITMEN ORGANISASI DAN MOTIVASI - Wedasari, Desy; Arizona, I Putu Edy (Jurnal Riset Akuntansi (JUARA), 2018)
Lembaga Perkreditan Desa (LPD) is a village-owned financial institution that is required for its managerial management. Some of the factors that can affect managerial performance are the participation of budgeting where by participating in the budgeting managers will feel responsible so that will improve managerial performance. Another factor that can affect is organizational commitment that is a belief not to leave the organization and motivation which is the impetus to work harder. This study aims to determine and prove empirically the influence of budgetary participation, organizational commitment, and motivation to managerial performance on all LPDs in Denpasar City and Badung regency. Data collection techniques using survey method and data analysis used is multiple linear regression. The results showed that the variable of budgetary participation, organizational commitment and motivation had a significant positive effect on the managerial performance of LPD.